Post-fascist Japan : political culture in Kamakura after the Second World War - Hein, Laura Elizabeth (SOAS studies in modern and contemporary Japan., 2018)
"In late 1945 local Japanese turned their energies toward creating new behaviors and institutions that would give young people better skills to combat repression at home and coercion abroad. They rapidly transformed their political culture-policies, institutions, and public opinion-to create a more equitable, democratic and peaceful society. Post-Fascist Japan explores this phenomenon, focusing on a group of highly educated Japanese - humanists, historians and social scientists -- based in the former capital and coastal city of Kamakura, where the new political culture was particularly visible. Many of these leftist elites had been seen as 'the enemy' during the war, making this project of domestic repair deeply personal for them. The book argues that they saw the problem as one of fascism, an ideology that had succeeded because it had addressed real problems. They turned their efforts to overtly political-legal systems but also to ostensibly non-political and community institutions such as universities, art museums, and local tourism and environmental policies, aiming not only for reconciliation over the past but also to reduce the anxieties that had drawn so many towards fascism. By focusing on a particular group of people in a particular place who had an outsized influence on Japan's political culture, Hein's study is both local and national. She grounds her theoretical discussion by using specific personalities, showing their ideas about 'post-fascism', how they implemented them and how they interacted with the American Occupiers. This is a unique, engaging and important study which will be extremely valuable for students and scholars of 20th-century Japanese intellectual, political and social history"--